A Multifunctional Hybrid Nanocarrier for Non-Invasive siRNA Delivery to the Retina - Shogo Nishida; Yuuki Takashima; Ryotaro Udagawa; Hisako Ibaraki; Yasuo Seta; Hiroshi Ishihara (MDPI AG, 2023)
Drug therapy for retinal diseases (e.g., age-related macular degeneration, the leading cause of blindness) is generally performed by invasive intravitreal injection because of poor drug delivery caused by the blood-retinal barrier (BRB). This study aimed to develop a nanocarrier for the non-invasive delivery of small interfering RNA (siRNA) to the posterior segment of the eye (i.e., the retina) by eyedrops. To this end, we prepared a hybrid nanocarrier based on a multifunctional peptide and liposomes, and the composition was optimized. A cytoplasm-responsive stearylated peptide (STR-CH2R4H2C) was used as the multifunctional peptide because of its superior ability to enhance the complexation, cell permeation, and intracellular dynamics of siRNA. By adding STR-CH2R4H2C to the surface of liposomes, intracellular uptake increased regardless of the liposome surface charge. The STR-CH2R4H2C-modified cationic nanocarrier demonstrated significant siRNA transfection efficiency with no cytotoxicity, enhanced siRNA release from endosomes, and effectively suppressed vascular endothelial growth factor expression in rat retinal pigment epithelium cells. The 2.0 mol% STR-CH2R4H2C-modified cationic nanocarrier enhanced intraocular migration into the retina after instillation into rat eyes.